Stages of Gold Deposits Formation in the Precambrian of the North-Eastern Fennoscandia - Arkadii A. Kalinin (Minerals, 2022)
Two main stages of formation of gold deposits are identified in the north-eastern part of the Fennoscandian Shield—Neoarchean (2.7–2.6 Ga) and Paleoproterozoic (1.92–1.74 Ga). These were the stages of rapid growth of the continental crust of the Earth and the consolidation of the ancient supercontinents, Kenorland in the Neoarchean, and Fennoscandia (or Columbia) in the Paleoproterozoic. Gold deposits and occurrences, which formed in the Archean (Oleninskoe and Nyalm in the Kolmozero–Voron’ya belt, and the Olenegorsk group of BIF deposits) were later metamorphosed in the Paleoproterozoic, and isotope data for the rocks and minerals of these deposits detect both Archean and Paleoproterozoic events. The Paleoproterozoic stage was the most important for the formation of gold deposits in the region, as at this stage the deposits formed not only in the Proterozoic greenstone belts, but in those Archean belts as well, which were involved in the Svecofennian tectonic processes in the Paleoproterozoic. As it is shown in the example of the deposits in the Central Lapland Paleoproterozoic belt, gold mineralization formed with a series of impulses of hydrothermal activity, and these impulses correlate with the formation of different generations of minor granite intrusions and dykes.